Pengaruh Doping Nikel dan Monoethanolamine (MEA) sebagai Zat Aditif terhadap Energi Celah Pita SnO2 - Nadya Alexandra; Hary Sanjaya; Alizar Ulianas; Umar Kalmar Nizar (Lembaga Yasin AlSys, 2026)
The relatively large band gap energy of SnO₂ semiconductors limits their ability to absorb visible light, resulting in suboptimal photocatalytic activity. Although modification of SnO₂ band gap energy through transition metal doping has been widely studied, research that specifically combines nickel doping with the addition of monoethanolamine (MEA) using the sol–gel method remains limited. This study aimed to analyze the effect of nickel doping and MEA addition on the band gap energy of SnO₂ synthesized via the sol–gel method. A quantitative approach with a laboratory experimental design was employed, in which pure SnO₂ and nickel-doped SnO₂ with MEA addition were synthesized as research samples and subsequently characterized using a UV–Diffuse Reflectance Spectrophotometer (UV–DRS). Reflectance data were analyzed using the Kubelka–Munk approach and Tauc plot method to determine band gap energy. The results showed that pure SnO₂ had a band gap energy of 3.59 eV, whereas nickel-doped SnO₂ with MEA addition exhibited a reduced band gap energy of 2.33 eV. These findings indicate that the combination of nickel doping and MEA additive is effective in modifying the optical properties of SnO₂ and extending its light absorption into the visible region, thereby enhancing its potential as a visible-light-driven photocatalytic material. This study contributes to the development of modification strategies for SnO₂-based oxide semiconductors and opens avenues for further research on optimizing dopant and additive compositions as well as directly evaluating the photocatalytic performance of the material.